Audiovisual perception of natural speech is impaired in adult dyslexics: An ERP study. (26th February 2015) - Rüsseler, J.; Gerth, I.; Heldmann, M.; Münte, T.F.
Highlights: Audiovisual integration of speech stimuli is impaired in dyslexic subjects. Audiovisual integration in dyslexics is less adaptive than in normal readers. Dyslexic subjects show an amplitude decrement for a face-sensitive ERP component. Abstract: The present study used event-related brain potentials (ERPs) to investigate audiovisual integration processes in the perception of natural speech in a group of German adult developmental dyslexic readers. Twelve dyslexic and twelve non-dyslexic adults viewed short videos of a male German speaker. Disyllabic German nouns served as stimulus material. The auditory and the visual stimulus streams were segregated to create four conditions: in the congruent condition, the spoken word and the auditory word were identical. In the incongruent condition, the auditory and the visual word (i.e., the lip movements of the utterance) were different. Furthermore, on half of the trials, white noise (45 dB SPL) was superimposed on the auditory trace. Subjects had to say aloud the word they understood after they viewed the video. Behavioral data. Dyslexic readers committed more errors compared to normal readers in the noise conditions, and this effect was particularly present for congruent trials. ERPs showed a distinct N170 component at temporo-parietal electrodes that was smaller in amplitude for dyslexic readers. Both, normal and dyslexic readers, showed a clear effect of noise at centro-parietal electrodes between 300 and 600 ms. An analysis of error trials reflecting audiovisual integration (verbal responses in the incongruent noise condition that are a mix of the visual and the auditory word) revealed more positive ERPs for dyslexic readers at temporo-parietal electrodes 200–500 ms poststimulus. For normal readers, no such effect was present. These findings are discussed as reflecting increased effort in dyslexics under circumstances of distorted acoustic input. The superimposition of noise leads dyslexics to rely more on the integration of auditory and visual input (lip reading). Furthermore, the smaller N170-amplitudes indicate deficits in the processing of moving faces in dyslexic adults.